2014
DOI: 10.1097/wnp.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

P300 Component of Event-Related Potentials in Persons With Asperger Disorder

Abstract: In the present study, we investigated auditory event-related potentials in adults with Asperger disorder and normal controls using an auditory oddball task and a novelty oddball task. Task performance and the latencies of P300 evoked by both target and novel stimuli in the two tasks did not differ between the two groups. Analysis of variance revealed that there was a significant interaction effect between group and electrode site on the mean amplitude of the P300 evoked by novel stimuli, which indicated that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Third, as for the P3 wave (which reflects a shift toward stimuli that requires a change in attention), some results show that there is no change in P3a amplitude in adults with ASD but there is an increased P3a amplitude in children with ASD ( Gomot et al, 2002 ; Ferri et al, 2003 ), other results show that there is an increased P3a amplitude in adults ( Iwanami et al, 2014 ). It seems that the amplitude of P3a is related to the subject’s age.…”
Section: Resultsmentioning
confidence: 99%
“…Third, as for the P3 wave (which reflects a shift toward stimuli that requires a change in attention), some results show that there is no change in P3a amplitude in adults with ASD but there is an increased P3a amplitude in children with ASD ( Gomot et al, 2002 ; Ferri et al, 2003 ), other results show that there is an increased P3a amplitude in adults ( Iwanami et al, 2014 ). It seems that the amplitude of P3a is related to the subject’s age.…”
Section: Resultsmentioning
confidence: 99%
“…At present, relatively few studies using EEG or magnetoencephalography to investigate sensory processing in ASD have investigated heterogeneity. No published neurophysiological studies have attempted to separate autistic individuals into subgroups based neural markers of sensory processing, although some studies have reported associations between neurophysiological responses and various other variables in ASD [29][30][31][32][33][34], including other measurements of sensory processing, such as questionnaires [35][36][37][38][39].…”
Section: Neurophysiologymentioning
confidence: 99%
“…Several previous studies of ASD patients have found inconsistent ERP abnormalities. For the P300 component, some studies have reported a shortened latency, 40 while others suggest prolonged latency 3,41 . Furthermore, the amplitude of P300 is similarly inconsistent, with some studies reporting a decrease in amplitude, 42–44 and others indicating an increase 17,41,45,46 .…”
Section: Discussionmentioning
confidence: 99%